Microbial electrocatalysis: Redox mediators responsible for extracellular electron transfer - Liu, Xiaobo; Shi, Liang; Gu, Ji-Dong (Biotechnology advances, 2018)
Redox mediator plays an important role in extracellular electron transfer (EET) in many environments wherein microbial electrocatalysis occurs actively. Because of the block of cell envelope and the low difference of redox potential between the intracellular and extracellular surroundings, the proceeding of EET depends mainly on the help of a variety of mediators that function as an electron carrier or bridge. In this Review, we will summarize a wide range of redox mediators and further discuss their functional mechanisms in EET that drives a series of microbial electrocatalytic reactions. Studying these mediators adds to our knowledge of how charge transport and electrochemical reactions occur at the microorganism-electrode interface. This understanding would promote the widespread applications of microbial electrocatalysis in microbial fuel cells, bioremediation, bioelectrosynthesis, biomining, nanomaterial productions, etc. These improved applications will greatly benefit the sustainable development of the environmental-friendly biochemical industries. •A diverse redox mediators involved in extracellular electron transfer (EET) are summarized.•The EET mechanisms of redox mediators are discussed.•Advances in biotechnological applications of microbial electrocatalysis are reviewed.•Future perspectives are provided for the EET studies.